Estimage: a webserver hub for the computation of methylation age. Issue Volume 49:Issue W1(2021) (26th May 2021) - Di Lena, Pietro; Sala, Claudia; Nardini, Christine
Abstract: Methylage is an epigenetic marker of biological age that exploits the correlation between the methylation state of specific CG dinucleotides (CpGs) and chronological age (in years), gestational age (in weeks), cellular age (in cell cycles or as telomere length, in kilobases). Using DNA methylation data, methylage is measurable via the so called epigenetic clocks . Importantly, alterations of the correlation between methylage and age (age acceleration or deceleration) have been stably associated with pathological states and occur long before clinical signs of diseases become overt, making epigenetic clocks a potentially disruptive tool in preventive, diagnostic and also in forensic applications. Nevertheless, methylage dependency from CpGs selection, mathematical modelling, tissue specificity and age range, still makes the potential of this biomarker limited. In order to enhance model comparisons, interchange, availability, robustness and standardization, we organized a selected set of clocks within a hub webservice, Esti m Age ( Esti mate of m ethylation Age, http://estimage.iac.rm.cnr.it ), which intuitively and informatively enables quick identification, computation and comparison of available clocks, with the support of standard statistics. Graphical Abstract: